Health consciousness and cervical cancer screening rates in HPV-unvaccinated girls: comparison from HPV-recommended and HPV-recommendation-suspended program periods - Ai Miyoshi; Yutaka Ueda; Asami Yagi; Mariko Taniguchi; Masayuki Sekine; Takayuki Enomoto; Tadashi Kimura (Taylor & Francis Group, 2021)
In Japan, the vast majority of females between 13 and 24 are now unvaccinated for HPV and thus unprotected from HPV-caused cervical cancer. We analyzed the differences among these unvaccinated females regarding their understanding of the HPV vaccine, its role in cervical cancer prevention, and their need for cervical cancer screening - based on whether they refused vaccination when their government's recommendation for HPV vaccination was still in effect (vaccination-recommended group) - or during the last 7 years, while the government suspension was in effect (recommendation-suspended group). The vaccination-recommended group understood more about the HPV vaccine and the best timing for HPV vaccination than the recommendation-suspended group (p < .0001 and p = .002, respectively). We found that girls in the vaccination-recommended group had more chances to talk with the family about cervical cancer and they were more afraid of acquiring the disease (p < .0001 and p < .0001, respectively). The girls in the recommendation-suspended group tended to feel more inhibited from talking about cervical cancer with friends and acquaintances (p = .0262). The cervical cancer screening rate of the vaccination-recommended group was significantly higher (p = .014).